Measurement and characterisation of glycans on surfaces - Oluwasanmi, Adeolu (2013)
Glycans are a diverse group of compounds, which include glycoproteins and glycolipids and are ubiquitously present on cell surfaces. As a result glycan interactions are responsible for a number of medical conditions such as autoimmune diseases like rheumatoid arthritis, viral infections and as a cause of inflammation. Fully understanding the structure and function of these compounds requires the use of innovative surface analytical methods for screening large numbers of different glycans against serums, for biomarkers attributed to these illnesses. The main objective of this work was to produce and characterise glycan surfaces with reliable, reproducible and quantitative readouts. However, the complex nature of glycans means that analysis of their interactions on microarray surfaces doesn’t always produce reliable readouts. The surfaces analysed also include commercially available amine coated slides for quality assurance and maleimide slides, which were produced by treating amine coated slides with 6-maleimidohexanoic acid N-hydroxysuccinimide ester (‘EMCS’ as denoted by Sigma Aldrich). Thiolated sugars can then react and covalently bond with the maleimide surfaces. Heterogeneous glycan immobilisation within spots is characterised using surface chemical analysis and compared to literature observation. The progress of the project titled “Measurement and Characterisation of Glycans on Surfaces” to date involved producing microarrays of β-D-thioglucose on a maleimide functionalised surface in order to see how phosphate buffered saline affected the surface chemistry and characterisation of the spots on the surface by using time of flight – secondary ion mass spectrometry.